Coronavirus Disease-2019 Vaccines and the Vaccination Challenges in India: A Review - Imran R. Rangraze; Shehla S. Khan; Yakub Sayyad (Internal Medicine, 2021)
The severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) designated as novel coronavirus is a cause of highly infectious disease referred to as coronavirus disease-2019 (COVID-19). The global pandemic that affected millions of people worldwide has claimed many lives and brought about catastrophe in low-income countries. The high mortality and rapid spread of the infection have brought about an urgent need for a safe and effective vaccine to control the pandemic. In this perspective, it becomes essential to understand the structure, mode of transmission, and virulence of SARS-Cov-2. In this article, an emphasis is made on understanding the infection pathogenesis and the host defense mechanisms against the infection to break the chain of transmission. Furthermore, we have tried to summarize the development and characteristics of different types of COVID-19 vaccines. In addition to this, we have highlighted the challenges of the public health system in the procurement and delivery of the vaccine to the community and especially to the most vulnerable society. It becomes the main priority to find support financially and make the public health system ready to imbibe the importance of vaccination through meticulous strategies so that vaccine reaches out to the community.